brand99
contestada

Indicate a general rule for the n th term of this sequence. 6 a , 3 a , 0, -3 a , -6 a , . . . an = 3 an + 9 a an = -3 an - 9 a an = -3 an + 9 a

Respuesta :

Finti

Answer:

an= -3 an + 9 a

Step-by-step explanation:

The first value in series is 6 a.

When we put n=1 in equation an=-3 a(1) +9 a

                                                   =6 a

The second term is having value of 3 a in the series.

When we put n=2 in equation an=-3 a(2) +9 a

                                                    =3 a

And so on,

So, an=-3 an +9 a